2005
DOI: 10.1007/s11179-005-0049-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and Primary Production in the Estuary of the Razdol’naya River (Amur Bay, Sea of Japan)

Abstract: The behavior of the basic nutrients (NO 3 , PO 4 , SiO 2 ) was studied in the estuary of the Razdol'naya River in low and high water, the flow was 4.3 × 10 6 m 3 /day and 10.8 × 10 6 m 3 /day, respectively. It was shown that within the limits of the euphotic zone the nutrients were characterized by a pronounced nonconservative behavior caused by their removal by phytoplankton in primary production. It was determined that phytoplankton removal of nutrients occurred with ratios ∆ C : ∆ NO 3 : ∆ P : ∆ Si = 105 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The highest chlorophyll a concentrations were found in the upper layers of the fresh water plume northward of the Lena Delta and freshened waters in the southeastern part of the Laptev Sea with high content of dissolved silicate. These findings are in agreement with the well-known fact that river plume supports higher production than surrounding shelf waters (Smetacek 1986;Zvalinsky et al 2005). The values of chlorophyll a estimated in our study are comparable to those reported for offshore zone of the Barents Sea (0.14-6 mg/m 3 ; Makarevich and Druzhkova 2010) and the freshened waters of the northwestern Kara Sea in early autumn (0.85-1.41 mg/m 3 ; Sukhanova et al 2012) as well as for the southeastern Laptev Sea at the beginning of the freeze-up (0.1-3.2 mg/m 3 ; Tuschling et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The highest chlorophyll a concentrations were found in the upper layers of the fresh water plume northward of the Lena Delta and freshened waters in the southeastern part of the Laptev Sea with high content of dissolved silicate. These findings are in agreement with the well-known fact that river plume supports higher production than surrounding shelf waters (Smetacek 1986;Zvalinsky et al 2005). The values of chlorophyll a estimated in our study are comparable to those reported for offshore zone of the Barents Sea (0.14-6 mg/m 3 ; Makarevich and Druzhkova 2010) and the freshened waters of the northwestern Kara Sea in early autumn (0.85-1.41 mg/m 3 ; Sukhanova et al 2012) as well as for the southeastern Laptev Sea at the beginning of the freeze-up (0.1-3.2 mg/m 3 ; Tuschling et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Although quantifying material fluxes from rivers to coastal regions is notoriously difficult [9], there is increasing interest in quantifying material fluxes into estuaries on global [16], regional [17], and local scales [5]. Knowledge of fluxes has been successfully used to study biogeochemical processes in estuaries and, particularly, to estimate primary production [18].…”
Section: Introductionmentioning
confidence: 99%